Síntese da manganês porfirina tetrarutenada e nanopartículas de ouro utilizadas para determinação voltamétrica de fármacos. - Vilarinho, Luana Moura (2017)
The present work performed the synthesis of 5, 10, 15, 20 - (tetrapyridyl) porphyrin or TPyP, which was used to coordinate the manganese ion in the porphyrin center. The porphyrin [Mn-TPyP]+, was left in reaction with the complexe mer - [RuCl3(dppb)(H2O)] to obtain the supramolecular specie {MnTPyP[RuCl3(dppb)]4}4+. All the complexes were characterized by ultraviolet and visible andinfrared absorption spectroscopy, where bands and characteristic stretches of the porphyrin complexes were presented. The supramolecular porphyrin was used to form films on the surface of the glassy carbon electrode, using the electropolymerization technique by cyclic voltammetry. The electrode modified with supramolecular porphyrin was used as an electrochemical sensor for simultaneous determination and quantification of ascorbic acid and paracetamol. Gold nanoparticles were synthesized by the Brust method, which is performed in a two-phase (toluene / water) system. The gold nanoparticles were immobilized with the supramolecular porphyrin, by electrostatic interaction, in order to obtain a modified electrode even more selective. The electrode modified with supramolecular porphyrin and gold nanoparticles was used to the simultaneous determination of ascorbic acid and dopamine. The modified electrodes when compared to the conventional electrode without the modification process, presented better responses for the studied analytes, where low detection and quantification limits were obtained, allowing them to be applied in real samples. PH, repeatability and interferences studies were performed to optimize as analysis conditions